**I am trying to find all the solutions and put them together at a single place, So feel free to add comments and if you have a solution please do post. Cheers … 🙂**

**Here is the puzzles link : http://www.wuriddles.com/**

**Question :**

“Proof” that 2 = 1:

a = b

a2 = ab

a2 – b2 = ab-b2

(a-b)(a+b) = b(a-b)

a+b = b

b+b = b

2b = b

2 = 1

Does this argument make sense?

**My Solution : **This is a wonderful question which tests our basics of Mathematics. In the school we might have studied that we can’t divide a number with zero. Though the concept is very clear, people often tend to forget that basic principle. Here if we carefully observe its given that :

a = b => a – b = 0

In the 4th step it is given that (a+b)(a-b) = b (a – b)

and we tend to write this step —— > b = (a+b) (a – b)/(a – b)

and cancel out (a – b), but (a -b) = 0. So we cant divide the product with (a – b) or cancel out (a – b).

Hence that is the erroneous statement……. 🙂

28.633921
77.364643

### Like this:

Like Loading...

*Related*

How about this solution??

0 * 1 = 0

0 * 2 = 0

=> 0 * 1 = 0 * 2

=> 1 = 2

hehe… 😛

lol ……… he he ….. 😛